Peran Mediasi Kepuasan Kerja Pada Pengaruh Iklim Organisasi Dan Pengembangan Karir Terhadap Kinerja Karyawan - Prayugo Yugo Pratama; Sjahril Effendy Pasaribu (Maneggio: Jurnal Ilmiah Magister Manajemen, 2020)
The purpose of this study is to analyze the influence of organizational climate and career development directly on employee performance, to analyze the direct effect of job satisfaction on employee performance and to analyze the indirect effect of organizational climate and career development on employee performance through job satisfaction. This research uses an associative approach method. The population and research sample are employees at PT. Angkasa Pura II (Persero) Kualanamu Branch Office in the Safey Riks Snd Quality Control Unit, totaling 42 people. In testing the hypothesis is done by using the Partial Least Square test. The results of this study indicate that directly organizational climate has no significant effect on job satisfaction and employee performance, career development has a positive and significant effect on job satisfaction and does not have a significant effect on employee performance, job satisfaction has no significant effect on employee performance. While the test indirectly states that organizational climate and career development affect employee performance through employee job satisfaction at PT. Angkasa Pura II (Persero) Kualanamu Branch Office.